Effect of 1,10-phenanthroline on DNA binding, DNA cleavage, cytotoxic and lactate dehydrogenase inhibition properties of Robson type macrocyclic dicopper(II) complex - Anbu, Sellamuthu (2020)
DNA targeting macrocyclic dicopper(II) complex, [Cu2L(H2O)2](phen)2(ClO4)2 (L = μ-11,23-dimethyl-3,7,15,19-tetraazatricyclo-[19.3.1.19,13,21] he p t a c o s a-1(24), 2, 7, 9, 11, 13(26), 14, 19, 21(25), 22-decaene-25,26-diol) (2), has been synthesized and characterized. This has been synthesized by reacting a Robson type macrocyclic precursor dicopper(II) complex [Cu2L(H2O)2](ClO4)2 (1) and 1,10-phenanthroline in ethanol. Solution ESR, electronic, and ESI-MS spectral studies suggest that 1,10-phenanthroline replaces coordinated water in 1, giving 2. The influence of the phenanthroline on DNA binding, cleavage, and anticancer properties of 2 have been investigated. Complex 2 displays better DNA binding and cleavage than 1. The dicopper(II) complexes 1 and 2 show cytotoxicity in human cervical HeLa cancer cells, giving IC50 values of 79.41 and 15.82 μM, respectively. Antiproliferative properties of 1 and 2 were confirmed by Trypan Blue exclusive assay and lactate dehydrogenase enzyme level in HeLa cancer cell lysate and content media.